THU0057 Inhibition of Heat Shock Protein 90 (Hsp90) Prevents Fibrosis by Targeting Canonical TGF-B Signaling. (23rd January 2014) - Tomcik, M.; Zerr, P.; Pitkowski, J.; Palumbo-Zerr, K.; Avouac, J.; Distler, O.; Becvar, R.; Haslbeck, M.; Senolt, L.; Schett, G.; Distler, J. H.
Abstract : Background: Heat shock protein 90 (Hsp90) has a crucial role in folding and conformational stabilization of TGF-β receptors and also of Src kinases, which are intracellular mediators of the pro-fibrotic effects of TGF-β. Inhibition of Hsp90 accelerates ubiquitination and increases proteasomal degradation of TGF-β receptors and Src. Thus, inhibition of Hsp90 may become a novel approach to target TGF-β signaling. Objectives: To evaluate the efficacy of Hsp90 inhibition as a novel approach for inhibition of aberrant TGF-β signaling and for the treatment of fibrosis in preclinical models of systemic sclerosis (SSc). Methods: The expression of Hsp90 was quantified by qPCR, Western Blot and immunohistochemistry. Collagen content was quantified by qPCR, SirCol collagen and hydroxyproline assay. The effects of Hsp90 inhibition by 17-DMAG (17-dimethylaminoethylamino-17-demethoxygeldanamycin) were analyzed in cultured fibroblasts, in bleomycin-induced dermal fibrosis, in tight-skin (Tsk-1) mice and in mice overexpressing a constitutively active TGF-β receptor I (TβRI). Mice were examined weekly for weight, activity and the texture of the fur. Results: The expression of Hsp90β was increased in SSc skin and in murine models of SSc in a TGF-β dependent manner. Inhibition of Hsp90 by 17-DMAG suppressed canonical TGF-β signaling and completely prevented the stimulatory effects of TGF-β on collagen synthesis and on myofibroblast differentiation. Treatment with 17-DMAG decreased the activation of canonical TGF-β signaling in murine models of SSc and exerted potent anti-fibrotic effects in bleomycin-induced dermal fibrosis, in Tsk-1 mice and in mice over-expressing a constitutively active TβRI. In bleomycin-induced dermal fibrosis, treatment with 17-DMAG reduced dermal thickening by 56±6% (p<0.001), hydroxyproline content by 81±28% (p<0.05) and myofibroblast counts by 65±12% (p<0.001). In Tsk-1 mice, 17-DMAG treatment reduced hypodermal thickening by 76±8% (p<0.001), hydroxyproline content by 67±17% (p<0.05) and myofibroblast counts by 85±10% (p<0.001). In mice overexpressing a constitutively active TβRI, 17-DMAG treatment reduced dermal thickening by 81±4% (p<0.001), hydroxyproline content by 88±36% (p<0.05) and myofibroblast counts by 69±16% (p<0.01). The treatment with 17-DMAG was well tolerated for up to 8 weeks at anti-fibrotic doses with no signs of toxicity such as weight loss, decreased activity or changes in the texture of the fur. Conclusions: Hsp90 is upregulated in SSc and is critical for TGF-β signaling. Pharmacological inhibition of Hsp90 by 17-DMAG effectively blocks the pro-fibrotic effects of TGF-β in cultured fibroblasts and in three different preclinical models of SSc. These results have translational implications, because several Hsp90 inhibitors are already evaluated in clinical trials for other indications. Acknowledgements: This study was performed with support of CMH Research Projects No 00000023728 Disclosure of Interest: None Declared